2010
DOI: 10.1016/j.marenvres.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and post-transcriptional response of drug-metabolizing enzymes to PAHs contamination in red mullet (Mullus barbatus, Linnaeus, 1758): A field study

Abstract: Aim of this study was to evaluate the responsiveness of red mullet (Mullus barbatus) liver detoxification enzymes to PAHs at transcriptional and post-transcriptional levels in the field. Fish were captured in the north-eastern Adriatic Sea, close to an oil refinery. Sixteen PAHs (EPA) were determined in sediments and fish fillets; transcription levels of cyp1a, cyp3a and abcc2 genes and EROD, BROD, B(a)PMO, BFCOD, GST and UDPGT enzymatic activities were measured. Levels of PAHs in sediments reflect the oil pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 51 publications
3
9
1
Order By: Relevance
“…Alteration of the ABC transporters in fish exposed to environmental pollutants (e.g., PAHs) has been reported (Christine Paetzold et al, 2009;Della Torre et al, 2010;Long et al, 2011;Costa et al, 2012). In this study, treatment with 100 g l −1 pyrene significantly induced the mRNA expression of the ABCC2 gene in the rare minnow liver ( Fig.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Alteration of the ABC transporters in fish exposed to environmental pollutants (e.g., PAHs) has been reported (Christine Paetzold et al, 2009;Della Torre et al, 2010;Long et al, 2011;Costa et al, 2012). In this study, treatment with 100 g l −1 pyrene significantly induced the mRNA expression of the ABCC2 gene in the rare minnow liver ( Fig.…”
Section: Discussionsupporting
confidence: 61%
“…4). In line with this, combined action and regulation of the biotransformation enzymes and ABC transporters has been reported in humans (Olinga et al, 2008) and several fish species (e.g., killifish, red mullet, and Nile tilapia) (Christine Paetzold et al, 2009;Della Torre et al, 2010;Costa et al, 2012). Moreover, Vollrath et al (2006) have described Nrf2-mediated co-regulation of MRP2 (ABCC2), GST, and GCLC.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In some previous studies, sex-related differences in P450 activity during the reproductive cycle have been reported in other fish (Andersson, 1990;Gray et al, 1991). Moreover, some previous studies showed a good correlation between EROD activity and CYP1A mRNA expression in fish (Quiró et al, 2007;Valdehita et al, 2012), but others also reported a poor correlation between EROD activity and CYP1A mRNA expression (Della Torre et al, 2010;Kammann et al, 2008;Karaca et al, 2014).…”
Section: Discussionmentioning
confidence: 92%